INNOVATIVE TEACHING METHODS FOR TODAY'S DIVERSE CLASSROOMS (Konferensiyalar | Conferences, 2024)
In today's dynamic educational landscape, characterized by increasing cultural diversity and technological advancement, educators are challenged to cultivate inclusive learning environments that cater to the diverse needs of students. This article explores the connection between modern pedagogical technologies and educational inclusivity, focusing on their application within the discipline of "Art Reading." Through an examination of innovative instructional methodologies such as visual incentives, gamified assessments, text-based activities, role-playing, interactive exercises, and flipped classroom models, we elucidate their effectiveness in enhancing student engagement, fostering critical thinking, and promoting cultural understanding. Drawing from empirical research and scholarly insights, this article underscores the transformative potential of modern pedagogical technologies in creating dynamic and inclusive learning experiences for students of diverse backgrounds and learning styles.